Consumer food environments change over a 5-year period - Patrícia Pinheiro de Freitas; Mariana Souza Lopes; Mariana Carvalho de Menezes; Patrícia Constante Jaime; Aline Cristine Souza Lopes (Cambridge University Press, 2024)
Abstract Objective: Evaluate the 5-year changes in the consumers' food environment in the area of a health promotion service in Brazilian primary health care. Our hypothesis is that the consumers' food environment in the areas with primary healthcare services has changes that may favour healthy eating habits over time. Design: Longitudinal study. Setting: The territory around the primary healthcare services in Belo Horizonte, Minas Gerais, Brazil. Participants: All food stores and open-air food markets that sell fruits and vegetables around the primary healthcare services in 2013 (n 272) and in 2018 (n 265). Results: Fruit diversity increased by 13·4 % (P < 0·001) and vegetables variety and quality by 16·1 % (P = 0·003) and 12·5 % (P < 0·001), respectively. Corn snacks showed an increase in availability (13·5 %; P = 0·002). The increase in advertising was observed for fruits and vegetables (34·6 %; P < 0·001) and ultra-processed foods (47·6 %; P < 0·001). Supermarkets showed an increase in the Healthy Food Store Index (three points; P < 0·001), while fruits and vegetables stores showed a decrease of one point in the index (P < 0·001). Conclusions: The unequal changes in the consumers' food environment according to the food stores types demonstrate the importance of food supply policies that promote a healthy environment and favour the maintenance of traditional healthy food retailers.